2018
DOI: 10.5114/aoms.2016.60227
|View full text |Cite
|
Sign up to set email alerts
|

The role of vitamin E in the prevention of zoledronic acid-induced nephrotoxicity in rats: a light and electron microscopy study

Abstract: IntroductionBisphosphonates are widely used in metastatic cancer such as prostate and breast cancer, and their nephrotoxic effects have been established previously. In this study we aimed to evaluate both the nephrotoxic effects of zoledronic acid (ZA) and the protective effects of vitamin E (Vit-E) on this process under light and electron microscopy.Material and methodsA total of 30 male Sprague-Dawley rats were divided into 3 groups. The first group constituted the control group. The second group was given i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Apoptosis induction may contribute to the pathophysiology of focal segmental glomerulosclerosis by bisphosphonates. [ 69 ] Also, it has been shown that zoledronic acid causes renal tubular cell death by apoptosis. [ 69 ] Similarly, the results of our study showed concentration‐dependent apoptosis induction.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis induction may contribute to the pathophysiology of focal segmental glomerulosclerosis by bisphosphonates. [ 69 ] Also, it has been shown that zoledronic acid causes renal tubular cell death by apoptosis. [ 69 ] Similarly, the results of our study showed concentration‐dependent apoptosis induction.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in the experimental animal study, 100% of rats presented histological renal lesions after intravenous bisphosphonate therapy [10]. These lesions were basal membrane thickness, cytoplasmic vacuolization, loss of brush border, tubular epithelial smoothness, tubular lumen obstruction and cell necrosis [10].…”
Section: Discussionmentioning
confidence: 98%
“…The mechanisms evoked for this nephrotoxicity are: the aggregation of bisphosphonates and calcium complexes in renal cells, and even more the induction by bisphosphonates of renal tubular cell death (similar to their apoptotic effect on osteoclasts) [10]. This is particularly due to the renal uptake and elimination of bisphosphonates [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paller score was used to describe histological changes 12 . Ten kidney tubules were randomly chosen under one vision to evaluate the histological score.…”
Section: Methodsmentioning
confidence: 99%